CIS 125 - Intro to Software Applications - Sisi Virasak (Linn-Benton Community College, 2018)
Designed to use technology as a productivity tool within a business environment through the use and integration of various software packages. Students will use word processing software for formatting business correspondence, creating tables, multipage documents, graphical elements, mail merge, and other features. Spreadsheet software will be used to create formulas, use built-in functions for calculations, create charts and graphs, reference other worksheets, create absolute and relative cell references as well as other formatting and editing features. Presentations software will be used to produce, edit, and create visually compelling presentations for business outcomes. Upon successful completion of this course, students will be able to: Apply word processing software features to produce, format, edit, and enhance business documents. Apply spreadsheet software features to create, edit, and format spreadsheets and charts Write formulas and use functions in spreadsheets to perform calculations for business scenarios. Apply presentations software features to produce, edit, and make visually appealing presentations.